2021
DOI: 10.3390/jmse9020159
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis of the Effect of Currents on the Dynamics of a Moored Flexible Cylindrical Net Cage

Abstract: A numerical model associated with wave–current interactions with a moored flexible cylindrical cage was developed based on the finite element method. An analytical model was formulated under the linearised wave theory and small structural response, and a semi-analytical solution was obtained using the Fourier Bessel series solution and least squares approximation method, along with a matching technique. The numerical results from the finite element analysis of the horizontal displacements for different design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…in which Q is the axial uniform tensile force in the net, m s is the uniform mass of the net per unit length, and ρ is the water density. In [28], a comparison between the analytical model based on Equation (10) and the FEM simulation for the cylindrical net cage illustrates acceptable errors.…”
Section: Methods Of Solutionsmentioning
confidence: 98%
See 2 more Smart Citations
“…in which Q is the axial uniform tensile force in the net, m s is the uniform mass of the net per unit length, and ρ is the water density. In [28], a comparison between the analytical model based on Equation (10) and the FEM simulation for the cylindrical net cage illustrates acceptable errors.…”
Section: Methods Of Solutionsmentioning
confidence: 98%
“…On the other hand, it is assumed that the cross-section of the cage maintains its circular shape under wave action if the cage is imposed a high axial tension and has a small deformation relative to its overall size. Liu et al [28] showed a deformed net cage simulated by the finite element method using truss elements, and it is observed that the cage approximately maintains a circular cross-section. Therefore, the transverse deflection of the cage is ζ = Re[η(z)e -iωt ], and the transverse vibration equation of the string to describe the complex amplitude η is given by Mandal and Sahoo [21]:…”
Section: Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results can be used to evaluate the fatigue life of the mooring ropes. Liu et al [8] described a numerical procedure to calculate the mooring forces and the cage motions for a gravity cage system.…”
Section: Introductionmentioning
confidence: 99%
“…Porous cylinders are also related to fish-farm cages, the performances of which, in currents and waves, have been widely studied in the literature. Noteworthy examples of recent works in chronological order are [44][45][46][47][48][49]. In these studies a porous flexible circular cylinder is assumed, simulating the fish net.…”
Section: Introductionmentioning
confidence: 99%